Electrical transport in nanoscale systems - Di Ventra, Massimiliano (Cambridge University Press, 2008)
This is a graduate textbook describing the transport phenomena in systems of nanoscale dimensions for students in physics, chemistry, and electrical engineering.
Keywords: Electron transport.; Electric conductivity.; Nanoelectronics.; Nanoelectromechanical systems.; elektronické knihy; electronic books